Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Inap Rumah Sakit Semen Padang - Bayu Ramadhan; Rahmiati Rahmiati; Arief Maulana (Universitas Negeri Padang, 2019)
Purpose - This study aimed to analyze: (1) the influence of reliability on inpatient satisfaction Hospital Semen Padang (2) the impact of responsiveness to satisfaction Hospital Semen Padang inpatient (3) the effect of assurance on inpatient satisfaction Hospital Semen Padang (4) the influence of empathy toward inpatient satisfaction Hospital Semen Padang (5) the effect of Physical evidence on inpatient satisfaction Hospital Semen Padang. Methodology - The population in this study is that patients Semen Padang Hospital. 100 people by using purposive sampling technique. Data using SPSS 21.Finding - The results of this study indicate that: (1) There is no significant effect Reliability of service quality to Inpatient Satisfaction Hospital Semen Padang (2) There is a positive and significant effect Responsiveness of Servqual forward in patient Satisfaction Hospital inpatient Semen Padang (3)Assurance of Servqual has positive and significant to Satisfaction of Hospital Semen Padang inpatient (4) There is a positive and significant influence between Empathy with Satisfaction Hospital Semen Padang inpatient (5) There is a positive and significant influence Physical Evidence with Satisfaction Hospital inpatient Semen Padang inpatient (6) Taken together between Reliability, responsiveness, assurance, empathy and Physical Evidence inpatient Satisfaction there is positive and significant at Semen Padang Hospital Keywords: Service quality, patient satisfaction, Semen Padang Hospital